Effect of Water Quality on Phytoplankton Structure in Oxbow Lakes under Anthropogenic and Non‐Anthropogenic Impacts. Issue 4 (4th October 2013) - Wilk‐Woźniak, Elżbieta; Ligęza, Sławomir; Shubert, Elliot
Abstract In this study, we present the effects of environmental factors on phytoplankton in two different oxbow lakes formed from the Vistula River. One of these lakes is under extreme anthropogenic pressure, i.e. impacted by industrial and municipal effluents and characterized by high water temperature and high concentrations of ions. The other oxbow lake is located in a natural forest with some its abiotic factors lower compared to the first oxbow lake. There were significant changes among environmental parameters, which influenced significant differences between the phytoplankton populations. The dominant algae of the impacted oxbow were small centric diatoms, which are able to rapidly absorb nutrients and have a rapid turnover. The results demonstrated that human impacted lake was a habitat, where species with a broad range of ecological requirements survive. However, these habitats are also more vulnerable for the entry and colonization of invasive algal species. In the forest oxbow lake, without human impact, heterogeneity of water quality parameters resulted in different specific habitats. Oxbow lakes are important as biodiversity hotspots for rare and/or endemic species.